Synthesis and Antimicrobial Activity of Novel 1-(4,5-Bioxadiazolyltriazolyl)/1-(4,5- bipyrrolylaminocarbonyl)/triazolyl)ethylindole/benz(g)indole - G. Bhovi, Manjunath; S. Gadaginamath, Guru (Asian Journal of Chemistry, 2016)
The exclusive formation of 1-[bis-4,5-hydrazinocarbonyl-1,2,3-triazol-1-yl]ethyl-3-ethoxycarbonyl-5-methoxy-2-methylindole 2 and 1-[bis-4,5-hydrazinocarbonyl-1,2,3-triazol-1-yl]ethyl-3-ethoxycarbonyl-5-methoxy-2-methylbenz(g)indole 8 from the reaction of 1-[4,5-dimethoxycarbonyl-1,2,3-triazol-1-yl]ethyl-3-ethoxycarbonyl-5-methoxy-2-methylindole 1 and 1-[4,5-dimethoxycarbonyl-1,2,3-triazol-1-yl]ethyl-3-ethoxycarbonyl-5-methoxy-2-methylbenz(g)indole 7 with hydrazine hydrate respectively revealed the chemoselectivity of the C4 and C5-esters of triazolylindole over that of C3-ester towards the nucleophilic attack of hydrazine hydrate. These dicarbohydrazides 2 and 8 were reacted separately with acetonyl acetone and CS2/KOH to secure 1-[4,5-bis(2,5-dimethylpyrrol-1- yl)aminocarbonyl-1,2,3-triazol-1-yl]ethyl-3-ethoxycarbonyl-5-methoxy-2-methylindole 5 and 1-[4,5-bis(2,5-dimethylpyrrol-1-yl)aminocarbonyl-1,2,3-triazol-1-yl]ethyl-3-ethoxycarbonyl-5-methoxy-2-methylbenz(g)indole 9 and 1-[4,5-bis(2,5-mercapto-1,3,4-oxadiazol-2-yl)-1,2,3-triazol-1-yl]ethyl-3-ethoxycarbonyl-5-methoxy-2-methylindole 6 and 1-[4,5-bis(2,5-mercapto-1,3,4-oxadiazol-2-yl)-1,2,3-triazol-1-yl]ethyl-3-ethoxycarbonyl-5-methoxy-2-methylbenz(g)indole 10 respectively. All these newly synthesized compounds were screened for their antimicrobial activities.